Hubungan Penguasaan Kosakata dengan Kemampuan Menulis Karangan Narasi Ekspostoris Siswa Kelas VII SMPN 2 Ampek Angkek - Rahmi, Fitri; Ratna, Ellya; Chan, Wirsal (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article was written to describe vocabulary of student, ability to write expository narrative, relation mastery of vocabulary with mastery ofÂ  write expository narrative. This research method is deskriptive. Data in this research is objectives result test for means vocabulary of ability student and performance tests in the form of write expository narrative essay for means of ability student to write expository narrative. Based on result of research, congcludes three things. First, mastery of vocabulary is at more than enough qualification (71,92). Second, ability to write expository narrative is at good qualification(81,55).third, there is significant relationship between mastery of vocabulary and mastery write expository narrative.